Detection of aberrant crypt foci with image-enhanced endoscopy - Kagemoto, Kaizo; Okamoto, Koichi; Takaoka, Toshi; Sato, Yasushi; Kitamura, Shinji; Kimura, Tetsuo; Sogabe, Masahiro; Miyamoto, Hiroshi; Muguruma, Naoki; Tsuneyama, Koichi; Takayama, Tetsuji (Endoscopy International Open, 2018)
Background and study aims Conventional detection of aberrant crypt foci (ACF) with dye-spraying and magnifying observation is labor- and skill-intensive. We performed a prospective non-inferiority study to investigate the utility of image-enhanced endoscopy (IEE) for detection of ACF. Patients and methods Patients with a history of colorectal neoplasm were eligible. The number of ACF in the lower rectum was counted first using IEE magnification with narrow-band imaging (NBI) or blue-laser imaging (BLI), and subsequently using the methylene blue method. The primary endpoint was the ACF detection rate with IEE, i. e., the number of ACF detected with IEE relative to the number of ACF detected with methylene blue. The secondary endpoints were bowel preparation time, ACF detection time, and the detection rate with NBI or BLI. Results A total of 40 patients were enrolled (NBI 20 and BLI 20). The overall detection rate for ACF with IEE was 81.7 % (503/616; 95 %CI 78.8 – 84.6 %), meeting the primary endpoint. The detection rate for ACF with BLI (84.9 %, 258/304) was significantly higher than with NBI (78.5 %, 245/312; P < 0.05). Both bowel preparation time and ACF detection time were significantly shorter with IEE versus the methylene blue method (P < 0.01, respectively). The detection rates for dysplastic and non-dysplastic ACF with IEE were 84.4 % (27/32) and 80.3 % (469/584), respectively. Conclusion IEE is able to detect ACF during colonoscopy with sensitivity non-inferior to that of the conventional methylene blue method. IEE is simpler than the methylene blue method and is therefore a potentially useful new tool for ACF detection.